Naphthalenediimide Polymers with Finely Tuned In‐Chain π‐Conjugation: Electronic Structure, Film Microstructure, and Charge Transport Properties. Issue 41 (30th August 2016) - Erdmann, Tim; Fabiano, Simone; Milián‐Medina, Begoña; Hanifi, David; Chen, Zhihua; Berggren, Magnus; Gierschner, Johannes; Salleo, Alberto; Kiriy, Anton; Voit, Brigitte; Facchetti, Antonio
Abstract : Naphthalenediimide‐based random copolymers (PNDI‐TVT x ) with different π‐conjugated dithienylvinylene (TVT) versus π‐nonconjugated dithienylethane (TET) unit ratios ( x = 100→0%) are investigated. The PNDI‐TVT x ‐transistor electron/hole mobilities are affected differently, a result rationalized by molecular orbital topologies and energies, with hole mobility vanishing but electron mobility decreasing only by ≈2.5 times when going from x = 100% to 40%.